2018
DOI: 10.1111/dom.13567
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of proximal and distal small intestinal administration of metformin on plasma glucose and glucagon‐like peptide‐1, and gastric emptying after oral glucose, in type 2 diabetes

Abstract: Aims The gastrointestinal tract, particularly the lower gut, may be key to the anti‐diabetic action of metformin. We evaluated whether administration of metformin into the distal, vs the proximal, small intestine would be more effective in lowering plasma glucose by stimulating glucagon‐like pepetide‐1 (GLP‐1) and/or slowing gastric emptying (GE) in type 2 diabetes (T2DM). Materials and methods Ten diet‐controlled T2DM patients were studied on three occasions. A transnasal catheter was positioned with proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 39 publications
4
40
3
Order By: Relevance
“…As reported previously, metformin increased plasma total GLP‐1 concentrations (i.e. the incremental area under the curve) and prolonged the gastric half‐emptying time ( P < 0.05 for each), when compared with control.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…As reported previously, metformin increased plasma total GLP‐1 concentrations (i.e. the incremental area under the curve) and prolonged the gastric half‐emptying time ( P < 0.05 for each), when compared with control.…”
Section: Resultssupporting
confidence: 82%
“…However, HR did not differ between the 2 study days in the current study, perhaps because of the varying duration of metformin therapy or route of glucose exposure (oral vs. ID). Interestingly, we observed that ID metformin slowed gastric emptying and increased plasma GLP‐1 levels, both of which are known to mitigate the postprandial BP fall . Moreover, metformin has been reported to inhibit small intestinal glucose absorption and improve left ventricular function, which may also be of relevance to the effects of metformin on postprandial BP …”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations